Pendidikan Islam Menjawab Tantangan Globalisasi - Rif’ah; Ummi Habibatul Islamiyah (Cyber Media Indonesia, 2022)
Islamic education has been faced with the challenges of globalization, which have a very good impact on individual life, social life, nation and state.. The purpose of Islamic education is to create a perfect human being physically and spiritually, achieve the happiness of the afterlife, devote yourself to Allah, carry out the duties of the caliph on earth and seek the pleasure of Allah. From that, learning is an obligatory. Ain obligatory for syari'ah knowledge, aqidah and akhlak-tasawuf as a basis for actualizing one's potential. Fardu kifayah for other sciences. In order to answer the challenges and fill opportunities in this globalization era, Islamic education needs to do several things: Preparing qualified human beings by providing qualified knowledge in accordance with their expertise while still upholding Islamic values. Institutionally, Islamic education must be able to innovate according to the needs, demands and developments of the times both in curriculum, governance, human resources, facilities and others. so that graduates of Islamic education institutions are ready to plunge in the midst of the global arena.